Can Standardisation of the Public Assessment Report Improve Benefit-Risk Communication? - Keyter, Andrea; Salek, Sam; Banoo, Shabir; Walker, Stuart (Frontiers in Pharmacology, 2020)
Background: National regulatory authorities (NRAs) make the decision to register a medicine based on an assessment of its benefits and risks and publicly available assessment reports are used as a tool to communicate the basis for the decision. The Universal Methodology for Benefit-Risk Assessment (UMBRA) has also been used to effectively communicate the basis of regulatory decisions. Many NRAs in emerging markets place reliance on the public assessment reports (PARs) of reference agencies to inform about their own regulatory decisions. However, PAR users often criticise the redacted nature of PARs and may be challenged in identifying key benefits and risks, value judgements and benefit-risk (BR) trade-offs. Methods: PARs for ertugliflozin l-pyroglutamic acid, erenumab and durvalumab published by regulatory bodies in Australia, Europe, Canada and the United States were compared with the validated UMBRA Benefit-Risk Template to evaluate the BR decision documentation. Published validation of UMBRA included report of a consortium of 4 regulatory authorities in Australia, Canada, Switzerland, and Singapore indicating that their clinical assessment templates were modified to align with the UMBRA approach. A focus group discussed the use of PARs as potential knowledge management tools for stakeholder understanding of regulatory decision making. The South African Health Product Regulatory Authority (SAHPRA) approach to document and communicate the BR decisions was evaluated. Results: Results indicate key elements to include in the PARs including regulatory history, an effects table and a record of the strengths and uncertainties for each benefit and risk. Focus group participants agreed that a harmonised PAR template would support improved regulatory decision-making transparency. SAHPRA communication of BR decisions could be improved through the use of the UMBRA BR Template as a guidance for BR assessment and the basis of the South Africa public assessment report format. Conclusion: SAHPRA’s use of a structured template that supports transparent and quality decision making could have a major impact in ensuring consistency in the BR assessment of new medicines. The implementation of this effective approach for communicating BR decisions will advance agency goals of being a trusted, responsive, accountable regulatory body in which all healthcare stakeholders may rely on with confidence.